2022
DOI: 10.1038/s41467-022-32533-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale segregation of channel and barrier claudins enables paracellular ion flux

Abstract: The paracellular passage of ions and small molecules across epithelia is controlled by tight junctions, complex meshworks of claudin polymers that form tight seals between neighboring cells. How the nanoscale architecture of tight junction meshworks enables paracellular passage of specific ions or small molecules without compromising barrier function is unknown. Here we combine super-resolution stimulated emission depletion microscopy in live and fixed cells and tissues, multivariate classification of super-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 77 publications
3
36
1
Order By: Relevance
“…These results are consistent with a recent study on claudin quinKO cells expressing human claudin-2, -15, and -10a conducted in parallel with this study (Gonschior et al, 2022). Furthermore, super-resolution microscopy demonstrated that claudin-2 and claudin-10a are segregated as patches but constitute continuous TJ strands overall in proximal tubules, suggesting that these pore-forming claudins assemble in a homophilic manner in vivo (Gonschior et al, 2022). Notably, the claudin-2-expressing cells showed larger PNa/PCl than the claudin-15-expressing cells.…”
Section: Reconstitution Of Tjs With Individual Claudin Subtypes In Cl...supporting
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with a recent study on claudin quinKO cells expressing human claudin-2, -15, and -10a conducted in parallel with this study (Gonschior et al, 2022). Furthermore, super-resolution microscopy demonstrated that claudin-2 and claudin-10a are segregated as patches but constitute continuous TJ strands overall in proximal tubules, suggesting that these pore-forming claudins assemble in a homophilic manner in vivo (Gonschior et al, 2022). Notably, the claudin-2-expressing cells showed larger PNa/PCl than the claudin-15-expressing cells.…”
Section: Reconstitution Of Tjs With Individual Claudin Subtypes In Cl...supporting
confidence: 94%
“…It was reported that the interaction of claudin-4 with claudin-8 is necessary for the localization of claudin-4 at TJs (Hou et al, 2010). Furthermore, two recent studies described that claudin-4 alone could not generate TJ strand-like structures when expressed in non-epithelial cells (Gonschior et al, 2022;Shashikanth et al, 2022). In contrast, claudin-4 reconstituted functional TJs in claudin quinKO cells in this study.…”
Section: Reconstitution Of Tjs With Individual Claudin Subtypes In Cl...supporting
confidence: 39%
See 1 more Smart Citation
“…Tight junctions (TJs) regulate paracellular permeability in epithelia and endothelia in a size- and charge-selective manner. These cell-cell junctions are defined by apparent fusion points of opposing cell membranes and meshworks of intramembranous fibrils (TJ strands), visualized by EM [1] , [2] , [3] and super-resolution light microscopy [4] , [5] . TJs represent multi-protein complexes including different membrane-associated scaffolding, signaling, and transmembrane proteins (mainly claudins, TAMPs, and JAMs).…”
Section: Introductionmentioning
confidence: 99%
“…3E and F ), in our case a desirable trait for examination of surface GPCRs. We aimed to push the boundaries of STED imaging, by looking at SNAP- and Halo-tagged Tubb5 9 and claudin10a, 15 where structures have constant diameters of 25 and 10 nm, respectively (Fig. S4, ESI † ).…”
mentioning
confidence: 99%